Pengembangan Berbagai Metode Analisis Kadar Natrium Siklamat Pada Minuman Ringan - Vriezka Mierza; Isyana Salsabila; Chalisya Vanya Advaita; Alfina Oktavianti; Sri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Sodium cyclamate is an artificial sweetener that is often circulated in the community. Sodium Cyclamate has the advantage of a higher sweetness level ± 30 times that of cane sugar or sucrose at a price that is relatively more affordable than natural sweeteners. However, excessive use of cyclamate can cause health problems. The maximum level of cyclamate use regulated in Permenkes 772/Menkes/Per/IX/88 is 3g/L for food and beverages. This article review aims to find out the various methods that can be used in determining the level of sodium cyclamate in soft drinks. The method used in this article review is a literature study with primary data in the form of national journals from the Google Scholar databases that have inclusion and exclusion criteria. The keywords used in the literature search process are